2021
DOI: 10.3390/cells10123282
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Bioenergetic and Proteomic Phenotyping Reveals Organ-Specific Consequences of Chronic Kidney Disease in Mice

Abstract: Chronic kidney disease (CKD) results in reduced kidney function, uremia, and accumulation of uremic metabolites. Mitochondrial alterations have been suggested to play a role in the disease pathology within various tissues. The purpose of this study was to perform a comprehensive bioenergetic and proteomic phenotyping of mitochondria from skeletal muscle (SkM), cardiac muscle (CM), and renal tissue from mice with CKD. The 5-month-old C57BL/6J male mice were fed a casein control or adenine-supplemented diet for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Altogether, we assumed that muscle wasting, malnutrition, and inflammation in the male subjects might contribute to markedly decreased serum iron bioavailability by upregulation of the iron regulatory hormone hepcidin [ 56 ]. As iron is essential for energy metabolism [ 3 ], it might induce unfavorable renal outcomes considering the high energy demand of the kidneys [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, we assumed that muscle wasting, malnutrition, and inflammation in the male subjects might contribute to markedly decreased serum iron bioavailability by upregulation of the iron regulatory hormone hepcidin [ 56 ]. As iron is essential for energy metabolism [ 3 ], it might induce unfavorable renal outcomes considering the high energy demand of the kidneys [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of iron deficiency are cognitive dysfunction [ 2 , 10 , 11 , 12 ], exacerbation of heart failure [ 9 , 13 , 14 ], impaired immune function [ 15 ], and decreased physical performance [ 1 , 15 ]. However, there is limited evidence exploring the effect of iron on renal function, even though the kidney is thought to possess high energy requirements [ 16 , 17 ]. Del Greco et al indicated that iron has a beneficial effect on kidney function in the general population [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial complex I functions is responsible for the oxidative phosphorylation-mediated ATP production and maintenance of a balanced mitochondrial respiratory chain [85]. In this condition, the mitochondrial Krebs cycle is involved in the oxidization of NADH for electron transfer for the reduction of ubiquinone to ubiquinol [86]. The alteration of the mitochondrial bioenergetics process is widely involved in the progression of CKD via oxidative stress and mitochondrial dysfunction [87].…”
Section: Discussionmentioning
confidence: 99%
“…References related to the methods used included previous studies. 25,[39][40][41][42][43][44][45][46][47]…”
Section: Data Availabilitymentioning
confidence: 99%